2017
DOI: 10.1007/s00264-017-3432-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intramedullary nail, plate, and external fixation in the treatment of distal tibia nonunions

Abstract: In this nonunion population, comminuted fracture types needed more time and revisions to reach union. Time to union was only clinically shorter when revision fixation was not performed, but IMN and PO were both successful fixation options with significantly shorter times to union than EF. Mean time to union increased even more when revision of fixation method was performed vs. exchange revision, as did nonunions with deep infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…No significant difference was found between external fixation and ORIF. Ebraheim NA et al reported that IMN can achieve better healing effect in the treatment of tibial fractures, comparing to ORIF and external fixation [149]. MIPPO had the lowest nonunion rate of all fixation modes.…”
Section: Discussionmentioning
confidence: 97%
“…No significant difference was found between external fixation and ORIF. Ebraheim NA et al reported that IMN can achieve better healing effect in the treatment of tibial fractures, comparing to ORIF and external fixation [149]. MIPPO had the lowest nonunion rate of all fixation modes.…”
Section: Discussionmentioning
confidence: 97%
“…This prospective study extends the indications for this novel SEIP technique from tibial shaft fracture to DTF. Currently, the primary interventions for treating DTF are IMN, locked plate, and external fixation [19,20]. The usage of the above surgical procedures depends on the fracture site, related fracture, ankle joint component, soft-tissue status, and patient's general health.…”
Section: Discussionmentioning
confidence: 99%
“…After the intramedullary nail is implanted, the surrounding bone tissue is compressed to form an elastic xation between the nail and the bone. At the same time, this procedure does not damage the blood supply in the fracture end [14][15][16][17][18][19] and help to accelerate the healing process [20,21]. This method becomes especially important for severe comminuted fractures due to its incomparable advantages over steel plates [16,18,[22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this procedure does not damage the blood supply in the fracture end [14][15][16][17][18][19] and help to accelerate the healing process [20,21]. This method becomes especially important for severe comminuted fractures due to its incomparable advantages over steel plates [16,18,[22][23][24][25] . Due to the above merits, interlocking intramedullary nails have become the rst-line treatment for unstable tibial fractures [26,27].…”
Section: Discussionmentioning
confidence: 99%